The role of bone marrow aspirate cells in the management of atrophic mandibular fractures by mini-invasive surgical approach: Single-institution experience. Issue 5 (May 2017) - Mannelli, Giuditta; Arcuri, Francesco; Conti, Marco; Agostini, Tommaso; Raffaini, Mirco; Spinelli, Giuseppe
Abstract: Purpose: The treatment of fractures involves addressing the biology of fracture repair and the mechanical stability of fracture fixation. Traditionally it has included the addition of bone graft to enhance healing. New advances in the understanding of the cellular and molecular mechanisms of fracture repair have led to the use of growth factors to accelerate bone healing. This study aimed to assess the advantages of autologous stem cell use for atrophic mandibular fracture treatment in comparison to standard technique. Materials and methods: A total of 35 patients (14 male and 21 female) were treated for fractures of atrophic mandibles between January 2011 and December 2014. Surgical technique provided mini-invasive open reduction with or without immediate homologous bone graft, while selected patients received autologous bone marrow aspirate cell grafts in addition to the standard treatment. Demographic data and details of treatment and outcomes were recorded. Results: Patients were categorized according to the use of autologous stem cells, leaving 17 patients treated with standard technique and autologous stem cells (Group A) and 18 treated with standard osteosynthesis only (Group B). Of the 35 patients, 26 had bilateral fractures; most patients had significant medical co-morbidities. Immediate bone graft was used in 37.1% of patients (7 in group A and 6 in group B). Complications occurred in 5 patients (14.3%). Two patients in group B (11.1%) showed non-union of the fracture. One patient in group A (5.8%) and one patient in group B (5.5%) showed wound dehiscence and were treated conservatively; one patient in group B had a local infection (5.5%), one out of 35 (2.8%), that was managed by prolonged antibiotic treatment. Conclusions: Despite the advanced age and medical co-morbidities of the vast majority of patients, mini-invasive open approach with autologous bone graft ensures a fast and excellent recovery. Moreover, the management of atrophic mandibular fractures by bone marrow aspirate cells is a safe and useful procedure which has a lower complication rate when compared to standard technique.